INFLUENCE OF SPEED, TIME OF HOMOGENIZATION, TYPE OF SURFACE ACTIVE SUBSTANCE ON THE SIZE OF PENTOXYPHILLINE NANOPARTICLES BASED ON POLY-DL-LAKTIDE-CO-GLICOLIDE - T. V. Timchenko; A. V. Blinov; A. V. Serov; L. I. Shcherbakova; V. A. Kompantsev; O. M. Мarkova; A. I. Medvetskiy; A. Y. Platonova (Фармация и фармакология (Пятигорск))
Nanopharmacology is a set of methods and techniques used in the creation, study, production and use of nanostructures (size about 1–700 nm) with new chemical, physical, and biological properties. For a long time pharmacologists have been working on molecular, and sometimes even on a submolecular level for synthesizing new drugs and explaining their mechanism of action. Thanks to this, the interest of pharmacology in nanotechnology is connected with new ways of obtaining and using medicines. One way of obtaining new forms of drugs is the synthesis of nanoparticles, since they allow the active substance to overcome the protective barriers of the body such as, for example, the immune system. Due to the fact that the surface of nanoparticles (nanocapsules) is multilayered, their resistance to the action of the protective mechanisms of the body increases, which allows the drug to retain the activity of the pharmacological action, as well as its structure for a longer time. The possibility of penetration through biological barriers, tissue-specificity, rate of drug release depends largely on the size and surface properties of nanoparticles.The aim of our study was to study the influence of such important factors as time, homogenization rate and the type of surface active substance, on the size of the obtained nanoparticles of pentoxifylline based on poly-DL-lactide-co-glycolide (PLGA).Materials and methods. The research was carried out using the information retrieval database (PubMed), as well as the results of our own research.Results and discussion. It has been found that the dispersion phase of the sample, in which polyvinyl alcohol was used as the surfactant, had the smallest size, particularly, the average hydrodynamic radius of the particles amounted to 175.4 nm. The influence of the speed and time of homogenization on the size of nano particles of pentoxifylline based on PLGA was experimentally proved. Also, microphotographs of nanoparticles of pentoxifylline based on poly-DL-lactide-coglycolide (PLGA) are presented.Conclusion.Our studies prove the effect of the speed and time of homogenization, as well as the type of surfactant, on the size of nanoparticles of pentoxifylline based on poly-DL-lactide-co-glycolide. As a result of the studies, the procedure for obtaining nanoparticles of pentoxifylline was adjusted.